2013
DOI: 10.1111/acer.12142
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department–Based Brief Intervention to Reduce Risky Driving and Hazardous/Harmful Drinking in Young Adults: A Randomized Controlled Trial

Abstract: Background Risky driving and hazardous drinking are associated with significant human and economic costs. Brief interventions for more than one risky behavior have the potential to reduce health-compromising behaviors in populations with multiple risk-taking behaviors such as young adults. Emergency department (ED) visits provide a window of opportunity for interventions meant to reduce both risky driving and hazardous drinking. Methods We determined the efficacy of a Screening, Brief Intervention, and Refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 50 publications
3
57
1
Order By: Relevance
“…Standardized role-play actors (SRAs) are extensively used to act as standardized patients in the field of medical education (Issenberg et al 2005; Sommers et al 2013) and are used to improve clinicians’ clinical and communication skills (Barrows 1993; Cohen et al 1996). SRAs were recruited from the Clinical Education Center at [Blinded University] to act as HR representatives during the role-plays.…”
Section: Methodsmentioning
confidence: 99%
“…Standardized role-play actors (SRAs) are extensively used to act as standardized patients in the field of medical education (Issenberg et al 2005; Sommers et al 2013) and are used to improve clinicians’ clinical and communication skills (Barrows 1993; Cohen et al 1996). SRAs were recruited from the Clinical Education Center at [Blinded University] to act as HR representatives during the role-plays.…”
Section: Methodsmentioning
confidence: 99%
“…We reported the primary results of the intervention elsewhere. 25 For this secondary analysis, we used data from the baseline assessment of the brief intervention and contact-control groups to assess the relationship between conduct behaviour problems before age 15 years, conduct behaviour problems after age 15 years, depressive symptoms, sleep, problem drinking and risky driving behaviours (drinking and driving, hostile, and reckless). Participants in the no-contact control group were not interviewed at baseline and, therefore, did not provide data for this analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…Using data from a randomised controlled trial (RCT) of an intervention to reduce risky driving and problem drinking, 25 the purpose of this secondary analysis was to examine relationships between multiple health-compromising behaviours and mental health factors with risky driving behaviours in late adolescents (ages 18-24 years) and adults (ages 25-44 years), including conduct behaviour problems before and after age 15 years, depressive symptoms, sleep, and problem drinking.…”
Section: Introductionmentioning
confidence: 99%
“…In a multi-hospital study across several states, it was found that 45% of adult ED patients were risky alcohol users (Sanjuan, et al 2014); this suggests that the ED may be a prime environment to identify and begin intervening with patients with a spectrum of alcohol use disorders (Brown et al 2012; Field et al 2010; Sommers et al 2013). Studies have investigated the feasibility and efficacy of using behavioral interventions in the ED setting to change drinking and driving behaviors.…”
Section: Introductionmentioning
confidence: 99%